Calcium interactions in amelogenin-derived peptide assembly - Zhang, Jing; Bai, Yushi; Wang, Jian; Li, Bing; Habelitz, Stefan; Lu, Jun-xia (Frontiers in Physiology, 2022)
Phosphorylation of serine residues has been recognized as a pivotal event in the evolution of mineralized tissues in many biological systems. During enamel development, the extracellular matrix protein amelogenin is most abundant and appears to be critical to the extreme high aspect ratios (length:width) of apatite mineral fibers reaching several millimeters in larger mammalian teeth. A 14-residue peptide (14P2, residues Gly8 to Thr21) was previously identified as a key sequence mediating amelogenin assembly formation, the domain also contains the native single phosphoserine residue (Ser16) of the full-length amelogenin. In this research, 14P2 and its phosphorylated form (p14P2) were investigated at pH 6.0 with various calcium and phosphate ion concentrations, indicating that both peptides could self-assemble into amyloid-like conformation but with differences in structural details. With calcium, the distance between 31P within the p14P2 self-assemblies is averaged to be 4.4 ± 0.2Å, determined by solid-state NMR 31P PITHIRDS-CT experiments. Combining with other experimental results, solid-state Nuclear Magnetic Resonance (SSNMR) suggests that the p14P2 self-assemblies are in parallel in-register β-sheet conformation and divalent calcium ions most likely connect two adjacent peptide chains by binding to the phosphate group of Ser16 and the carboxylate of Glu18 side-chain. This study on the interactions between calcium ions and amelogenin-derived peptides provides insights on how amelogenin may self-assemble in the presence of calcium ions in early enamel development.